Neonatal infection with Bordetella pertussis promotes autism-like phenotypes in mice - Mills, Kingston; Lynch, Marina; Moran, Barry (My University, 2025)
Autism spectrum disorder (ASD) has been linked with infections early in life. Here we demonstrate that the infection of neonatal mice with the respiratory pathogen Bordetella pertussis leads to neuroinflammation, neurodevelopmental defects, and ASD-like behaviors. Following the respiratory challenge of neonatal mice with B. pertussis, multiple atypical CNS findings were observed, including blood-brain barrier disruption, dissemination of live B. pertussis bacteria to the brain with the concomitant infiltration of inflammatory monocytes, neutrophils, and activated IL-17A- and IFN-g-producing CD4 T cells. Microglia from infected mice were activated, with impaired phagocytic function, resulting in defective synaptic pruning and disrupted neuronal circuit formation. Impaired neurodevelopment in B. pertussis-infected post-natal mice was associated with ASD-like behavioral abnormalities in young adulthood. Our data indicate that infection with virulent B. pertussis during infancy increases the risk of autism-like behavior in young adult mice. A study into the potential role of B. pertussis in human ASD is warranted.
PUBLISHED
Cited by: 2; All Open Access, Green Open Access